Biosynthesis of Secondary Metabolites Based on the Regulation of MicroRNAs. (4th March 2022) - Hossain, Rajib; Quispe, Cristina; Saikat, Abu Saim Mohammad; Jain, Divya; Habib, Arslan; Janmeda, Pracheta; Islam, Muhammad Torequl; Radha,; Daştan, Sevgi Durna; Kumar, Manoj; Butnariu, Monica; Cho, William C.; et al.
Abstract : MicroRNA (miRNA), a noncoding ribonucleic acid, is considered to be important for the progression of gene expression in plants and animals by rupture or translational repression of targeted mRNAs. Many types of miRNA regulate plant metabolism, growth, and response to biotic and abiotic factors. miRNA characterization helps to expose its function in regulating the process of post-transcriptional genetic regulation. There are a lot of factors associated with miRNA function, but the function of miRNA in the organic synthesis of by-products by natural products is not yet fully elucidated. The current review is aimed at observing and characterizing miRNAs and identifying those involved in the functioning of the biosynthesis of secondary metabolites in plants, with their use in controlled manipulation.